Stress evolution during growth of 1-D island arrays: Kinetics and length scaling. (1st March 2015) - Chason, E.; Engwall, A.M.; Miller, C.M.; Chen, C.-H.; Bhandari, A.; Soni, S.K.; Hearne, S.J.; Freund, L.B.; Sheldon, B.W.
Abstract : To explore the mechanisms controlling residual stress in thin films, we have measured the stress evolution during electrodeposition of Ni on lithographically patterned substrates with different pattern spacings and growth rates. Studying films with a controlled island geometry allows us to relate the stress (measured using wafer curvature) to the evolution of the morphology. We analyze the measurements with a model that focuses on the stress that develops where adjacent islands grow together to form new elements of grain boundary.